2022
DOI: 10.3390/app12146897
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Mode Control of Electro-Hydraulic Position Servo System Based on Adaptive Reaching Law

Abstract: For the problem of the system state variable taking a long time to reach the sliding mode surface and the chattering frequency being high in the sliding mode surface, a sliding mode control method based on the adaptive reaching law is proposed, the system state variable is introduced based on the subreaching law, and an improved variable-speed reaching law is added with reference to the characteristics of the hyperbolic tangent function. The sliding mode control method is divided into two stages, namely, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…In Section 3, the control law was derived by an analytical method. Based on this, some parameters were adjusted by referring to some literature [41,42] and combining with our model. 6 × 10 4 q 3 4 × 10 6 q 4 1 × 10 8…”
Section: Simulation and Experimental Results And Discussion Of The Pn...mentioning
confidence: 99%
“…In Section 3, the control law was derived by an analytical method. Based on this, some parameters were adjusted by referring to some literature [41,42] and combining with our model. 6 × 10 4 q 3 4 × 10 6 q 4 1 × 10 8…”
Section: Simulation and Experimental Results And Discussion Of The Pn...mentioning
confidence: 99%
“…Additionally, the parameters r 0 , r 1 , r 2 , r 3 , r 4 , r 5 , and r 6 refer to the centers of the membership functions of the output variable's linguistic states Z, PS, PM, PB, NS, NM, and NB, respectively. To specify these parameters, we employ the following selections in Equation (29).…”
Section:  mentioning
confidence: 99%
“…Comparing their fault-tolerant controller with another QFT controller synthesized without considering the leakage fault, the simulation results showed that the fault-tolerant QFT controller could achieve the prescribed specifications even with internal leakage up to 8.6 L/min, thus confirming its effectiveness and reliability. Similarly, Sun, Dong, Wang, and Li [29] proposed dynamic models for the valve-controlled asymmetric hydraulic cylinder, and a simplified mathematical model of the electrohydraulic position servo system was determined by ignoring the nonlinear factors of the servo valve. They designed a novel sliding mode control (SMC) method based on the adaptive reaching law to control the displacement and velocity of the piston.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the first part of the control law is to reach the sliding mode surface and the second part with a discontinuous term is to keep the state variables inside it. For example, Sun et al [10] use an adaptive reaching law in the SMC to quickly track the desired position of a hydraulic cylinder. Asymptotic convergence in the sliding surface is ensured using the sign function as is shown in the work (Zheng and Su [11]).…”
Section: Introductionmentioning
confidence: 99%